A comparative study of the flexural performance of hybrid-reinforced (glass fiber reinforced polymer and steel bars) concrete beams before and after exposure to chloride environment. Issue 6 (April 2022) - Lu, Chunhua; Yang, Yuting; Ruan, Xiangjie; Wu, Xiaolong
To investigate the flexural performance of hybrid-reinforced concrete (HRC) beams before and after exposure to chloride environment comparatively, 12 HRC beams with two types of reinforcements of glass fiber reinforced polymer (GFRP) bars and steel bars, and four steel-reinforced concrete (SRC) beams were fabricated. Based on definitions of the balanced reinforcement ratio and the appropriate HRC beam, the calculation model of the flexural capacity of HRC beams after exposure to chloride environment was proposed in this study. The experimental results verified the validity of the plane section assumption on all test HRC beams. It is found that the deflection of unconditioned HRC beams increases faster than that of unconditioned SRC beams but slower than that of conditioned HRC beams exposed to chloride environment. Besides, the flexural capacity of conditioned HRC beams decreases due to the exposure and the retention ratio of flexural capacity correlates positively with the ratio of nominal reinforcement ratio converted by the elastic modulus to balanced reinforcement ratio converted by the elastic modulus ( ρ nom, E / ρ b, E ). The good agreement between the predicted values of flexural capacity and measured ones shows the applicability of the calculation model proposed for HRC beams.